Aplikasi Teori Betty Neuman dalam Asuhan Keperawatan pada Kasus Luka Dekubitus dengan Hemiparese Pasca Stroke - Purnamasari, Yeni; Nursanti, Irna (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
The Neuman Theory emphasizes a holistic system view of individuals, regarding them as systems interacting with their environment. In the context of patients with hemiparesis and decubitus ulcers, the concept of internal and external stressors is applied to identify factors affecting health. This approach enables nurses to provide comprehensive care, focusing on the overall recovery of the patient.